(untitled) (gjstudies, 2025)
This research examines the critical role of Information Systems (IS) auditors inimplementing Governance, Risk, and Compliance (GRC) frameworks within banking information systems to maintain financial integrity and prevent fraud. Througha mixed-methods approach combining quantitative analysis of banking sector dataand qualitative interviews with IS auditing professionals, this study develops a comprehensive model that demonstrates how effective GRC implementation correlateswith reduced financial irregularities and enhanced compliance outcomes. The research analyzes data from 150 financial institutions over a five-year period, revealingthat organizations with mature GRC frameworks experience 42% fewer security incidents and 67% faster compliance reporting cycles. The study introduces a novelGRC Maturity Assessment Framework that quantifies the relationship between ISauditing practices and financial integrity metrics. Findings indicate that IS auditors’ technical expertise in cybersecurity controls, data analytics, and regulatoryrequirements significantly enhances the alignment between technology governanceand fraud prevention objectives. The research contributes to both theoretical understanding and practical implementation of GRC frameworks in the banking sector,providing actionable insights for financial institutions seeking to strengthen theirfinancial integrity through improved information systems governance.